Abu Reyhan Biruni (973-1048 CE): The Pioneer in Clarifying the Role of Pharmacy in Medical Practice - Mahya Roohnavaz; Halil Tekiner; Mohammad Reza Shams Ardakani; Arman Zargaran (Tehran University of Medical Sciences, 2022)
Abu Reyhan Biruni (973-1048 CE) was a Persian polymath in medieval era. He had more than 100 books and treatises on different subjects like astronomy, culture, history, mathematics and pharmacy. In medical sciences, he was one of the first persons who introduced pharmacy as a separated field from medicine. He was pioneer to define pharmacy and pharmacist similar to current definitions. It was one of the earliest definitions of pharmacy. Biruni can be introduced as a pharmacist, nor physician. He also had a book on pharmacy, Al-Saydana fi al-Tibb (Pharmacy in Medicine). This book is one of the most important works on pharmacy in medieval era. He clarifies the role of pharmacists to serve pharmaceutical services to the patients. It shows the importance of pharmacy as an independent field of medical sciences in Persia and Islamic civilization about a thousand years ago.